Postoperative complications of pulmonary resection. Issue 11 (November 2020) - Thorpe, A.; Rodrigues, J.; Kavanagh, J.; Batchelor, T.; Lyen, S.
Abstract : Thoracic surgery has seen a resurgence in recent years with increasing numbers of cases taken on since the mid-2000s. There has been a paradigm shift in how we manage lung cancer with more emphasis on surgical resection, and this has been aided by minimally invasive video-assisted thoracic surgery (VATS) techniques. As a result, the prevalence of postoperative findings and complications is also increasing, and it is increasingly important for the general radiologist to recognise and diagnose these conditions as thoracic surgical patients may present acutely to non-thoracic surgical institutions. This review will cover both the early and late complications following a variety of lung resection surgeries.